Effects of rivastigmine on gait in patients with neurodegenerative disorders: A systematic review and meta-analysis - Shim, Sung Ryul; Kim, Jong-Yeup; Kwon, Kyum-Yil; Shin, Jieun; Lee, Yungjin; Lee, Seon-Min (PloS one, 2024)
Gait disturbances are commonly observed in patients with neurodegenerative disorders, including Alzheimer's disease, Parkinson's disease, and higher-level gait disorders, which are associated with cholinergic deficits. We conducted a systematic review and meta-analysis to investigate the effects of rivastigmine on improvement in gait. A comprehensive literature search was conducted using Medical Subject Heading (MeSH) terms and text keywords related to gait and falls after rivastigmine treatment for neurodegenerative disorders. The intervention (rivastigmine), comparison (control or no treatment), and outcomes of improvement in gait speed and fall were assessed from database inception to April 2024. References and collected data were meticulously reviewed to ensure the integrity of the included studies. Standardized mean differences (SMDs) and Hedges'g, along with their 95% confidence intervals (Cls), were calculated for gait speed and number of falls. A total of 222 articles were identified during the initial search across different electronic databases, 50 including PubMed (n = 23), Cochrane (n = 19), Embase (n = 139), Scopus (n = 38), and a manual search (n = 3). Finally, we conducted a systematic review and meta-analysis focusing on the final four studies, encompassing 286 participants. The pooled SMD for the overall gait speed without a comparison group was 0.761 (95% CI: -1.165 to 2.688), indicating no significant improvement in gait speed. For the overall number of falls between the rivastigmine treatment and control groups, the pooled SMD was -0.366 (95% CI: -0.650 to -0.083). A statistically significant reduction in the number of falls was observed in the rivastigmine group than in the control group. Rivastigmine treatment in patients with neurodegenerative disorders tend to improve gait speed and significantly reduces fall incidence. Given the limited efficacy of current treatments for gait disturbances and falls, dual cholinesterase inhibitors like rivastigmine could be a promising therapeutic option.